Brand new experience: the emergent marketplace - Lenderman, Max (Henry Stewart Talks, 2009)
Just how impressive is the emerging marketplace of hyper-developing countries?, What is experiential marketing?, Two big themes: brand and consumer, The experience of brand authenticity, The experience of consumer engagement